Detection of Pseudomonas aeruginosa metabolite pyocyanin in water and saliva by employing the SERS technique - Zukovskaja, Olga; Jahn, Izabella Jolan; Weber, Karina; Cialla-May, Dana; Popp, Jürgen (Sensors, 2017)
Pyocyanin (PYO) is a metabolite specific for Pseudomonas aeruginosa. In the case of immunocompromised patients, it is currently considered a biomarker for life-threating Pseudomonas infections. In the frame of this study it is shown, that PYO can be detected in aqueous solution by employing surface-enhanced Raman spectroscopy (SERS) combined with a microfluidic platform. The achieved limit of detection is 0.5 µM. This is 2 orders of magnitude below the concentration of PYO found in clinical samples. Furthermore, as proof of principle, the SERS detection of PYO in the saliva of three volunteers was also investigated. This body fluid can be collected in a non-invasive manner and is highly chemically complex, making the detection of the target molecule challenging. Nevertheless, PYO was successfully detected in two saliva samples down to 10 µM and in one sample at a concentration of 25 µM. This indicates that the molecules present in saliva do not inhibit the efficient adsorption of PYO on the surface of the employed SERS active substrates.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Artificial sputum; Diagnosis; Microfluidics; Pyocyanin; SERS